Upaya meningkatkan hasil belajar sejarah kebudayaan Islam dengan menggunakan metode role playing - Siti Aisyah (Persatuan Guru Republik Indonesia Kota Banjarbaru, 2021)
The world of education is experiencing developments in creating a young generation that is able to face globalization. Various efforts have been made to achieve the goals of education in Indonesia. One of them is making educational curricula, both at the level of Kindergarten, Elementary School, Junior High School, General High School, and even Higher Education. One of the subjects that must be delivered to students is Islamic Religious Education (PAI). According to Suparno (2002), students who are active in the learning process are characterized by two activities, namely activities in thinking (minds on) and activities in doing (hands on). The real actions of students in learning are the result of the involvement of students' thinking in their learning activities. Thus the process of understanding students in conveying the material must be truly acceptable. Especially in PAI subjects. Because the scope of PAI there are three main learning points, namely faith, worship and Sufism. Meanwhile, at the elementary school level, the competencies include the Koran and Hadith, faith, worship, and Islamic Cultural History. Especially for class V, at this level PAI learning already contains in-depth Islamic religious material. Therefore, students are expected to always be able to understand and understand the material presented by the teacher. The research method is a method used by researchers in collecting research data (Ari Kunto 2006: 2). In accordance with the problem being studied, the type of research conducted by the researcher is in the form of classroom action research (CAR). CAR is a part of action research conducted by teachers in the classroom and aims to improve and improve the quality and quantity of the learning process in the classroom (Iskandar 2009: 20). Based on the results of research conducted at SDN SN Karang Mekar 1, Banjarmasin Timur District, Banjarmasin City, it can be concluded that the use of the Role Playing method can improve student learning outcomes in PAI subjects, especially in the material History of Islamic Culture in class V students at SDN SN Karang Mekar 1 East Banjarmasin District, Banjarmasin City 2018/2019 Academic Year.